Co-housing of Rift Valley Fever Virus Infected Lambs with Immunocompetent or Immunosuppressed Lambs Does Not Result in Virus Transmission - Wichgers Schreur, Paul J.; van Keulen, Lucien; Kant, Jet; Oreshkova, Nadia; Moormann, Rob J. M.; Kortekaas, Jeroen (Frontiers in Microbiology, 2016)
Rift Valley fever virus (RVFV) is transmitted among susceptible animals by mosquito vectors. Although the virus can be isolated from nasal and oral swabs of infected animals and is known to be highly infectious when administered experimentally via oral or respiratory route, horizontal transmission of the virus is only sporadically reported in literature. We considered that immunosuppression resulting from stressful conditions in the field may increase the susceptibility to horizontally transmitted RVFV. Additionally, we reasoned that horizontal transmission may induce immune responses that could affect the susceptibility of contact-exposed animals to subsequent infection via mosquito vectors. To address these two hypotheses, viremic lambs were brought into contact with sentinel lambs. One group of sentinel lambs was treated with the immunosuppressive synthetic glucocorticosteroid dexamethasone and monitored for signs of disease and presence of virus in the blood and target organs. Another group of contact-exposed sentinel lambs remained untreated for three weeks and was subsequently challenged with RVFV. We found that none of the dexamethasone-treated contact-exposed lambs developed detectable viremia, antibody responses or significant increases in cytokine mRNA levels. Susceptibility of immunocompetent lambs to RVFV infection was not influenced by previous contact-exposure. Our results are discussed in light of previous findings.